2011
DOI: 10.18673/gs.v2i2.24273
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de programa para mudança do estilo de vida sobre a percepção de saúde em adultos

Abstract: O objetivo do presente estudo foi avaliar a percepção subjetiva dos indivíduos participantes de um programa de MEV de longa duração, com benefícios evidentes na aptidão física, relativos na obesidade e não detectados na alimentação. Dos 104 indivíduos (54, 04 ± 7,7 anos) 74% mulheres que frequentaram o programa com exercícios físicos/aconselhamento alimentar durante 2 anos, realizou-se subamostra aleatória de 24 indivíduos (16 mulheres e 8 homens) com entrevista aberta não-estruturada, contendo uma questão nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Nearly half of subjects exceeded the first six months in the program, result also reported in literature 17 , and in the present study, the highest dropout rate occurred during the first year of intervention. High dropout rate particularly in the first six months was also observed in a study on subjects enrolled in a long-term changing lifestyle program 22 . Due to the low frequency of those who remain in the first months, ACSM 21 draws the attention of physical education professionals and health administrators to take measures to reduce dropout in the initial period of PA programs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nearly half of subjects exceeded the first six months in the program, result also reported in literature 17 , and in the present study, the highest dropout rate occurred during the first year of intervention. High dropout rate particularly in the first six months was also observed in a study on subjects enrolled in a long-term changing lifestyle program 22 . Due to the low frequency of those who remain in the first months, ACSM 21 draws the attention of physical education professionals and health administrators to take measures to reduce dropout in the initial period of PA programs.…”
Section: Discussionmentioning
confidence: 53%
“…The results showed that two thirds (68%) of participants dropped out within the 3 rd time interval, approximately one year. A study evaluating individuals in a long-term changing lifestyle program concluded that 47% of participants remained at least one year in the program 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Resultado este, que se observou na pesquisa do autor acima, pois 94% dos adolescentes relacionaram a melhora da AE com a prática da musculação. 30 Esses dados encontrados se assemelharam com os de Coelho-Ravagnani, 31 em estudo sobre o efeito de programa de musculação para mudança do estilo de vida sobre a percepção de saúde em adultos, demonstrando que 96% dos entrevistados mencionaram mudanças relacionadas à dimensão física, 67% nas psicológicas e 83% em dimensão social.…”
Section: Resultsunclassified
“…Embora os resultados do Programa tenham trazido melhorias das variaveis clinicas e, tambem sensacoes de bem estar aos concluintes, chama a atencao, a queda de aderencia a longo prazo: 65% em 10 semanas, 52,3% 3m 24 semanas, 47% em 12 meses, 12,% em 2 anos e 6,3% em 3 anos. (Coelho et al 2011). Agora, mediante o questionario SF-36 eespera-se dimensionar a qualidade de vida experimentada pelos concluintes da intervenção pelo programa de mudança de estilo de vida, nos resultados destes domínios do SF-36.…”
Section: Palavras-chaveunclassified